Inculturation of Familiaris Consortio in Family-Based Christian Sexuality Education within Dayak Local Wisdom - Avan, Komela; Lorensius, Lorensius; Ubeq, Victoria Julianti Siska (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study specifically aims to investigate how Catholic families in Long Bagun, Mahakam Hulu Regency, East Kalimantan Province, interpret, adapt, and apply the principles of Christian moral sexuality education prescribed by Familiaris Consortio (FC) within the framework of Dayak local wisdom, in order to identify culturally grounded pedagogical strategies that support family-based catechesis and moral formation. This study employed a qualitative case study with an ethnographic approach, collecting data through in-depth semi-structured interviews, document analysis, and informal observations from December 2024 to April 2025, and analyzing them using thematic analysis to identify patterns of how Catholic families integrate Christian moral sexuality education with Dayak local wisdom. Findings reveal that the Church’s core principles of open, gradual, and integral formation are conveyed less through formal texts and more through culturally resonant pedagogies such as storytelling, exemplary living (teladan), communal practices of gotong royong, respect for elders, and the social moral grammar of malu. The Dayak sacred understanding of the body and nature serves as a bridge to Pope John Paul II’s Theology of the Body, reframing chastity as stewardship of a God-given “field” (ladang) entrusted to each person for the good of family and community. Parents creatively address cultural taboos and the challenges of digital media by embedding moral conversations in daily routines and community rituals, positioning the village as co-educator and the family as a vibrant “domestic church.” The study contributes to faith education by offering culturally grounded strategies for family catechesis based on local narratives, inculturated modules in marriage preparation, and peer learning groups for parents to strengthen policy and program design in multicultural Catholic education.